A Review of Taxonomic Perspective of Diversity in Gymnosperms of Kashmir Himalaya: Review: Diversity in Gymnosperms (Biological Sciences - PJSIR, 2021)
Varied floristic works relevant to Kashmir Himalaya were thoroughly examined to compile taxonomic contributions of various taxonomists viz. a viz. diversity in gymnosperms of this region. Extensive field surveys and standard taxonomic methods were used to locate, collect, identify and prepare an updated list of the target group. A total of 25 species of gymnosperms belonging to 13 genera in 6 families and 4 orders have been documented from the Kashmir Himalaya. Wild gymnosperms are represented by 11 species with conifers forming the most dominant group. Among families, Pinaceae is highest represented with 6 species, while Taxaceae is least represented. Cultivated gymnosperms exceed wild growing species, and Cupressaceae is most dominant with 9 species whereas Ginkgoaceae is least represented. Out 25 species 19 (7 wild + 12 cultivated) are trees, 5 (3 wild + 2 cultivated) are shrubs and only 1 is sub-shrub.